Taming microwave plasma to beat thermodynamics in CO2 dissociation. (21st September 2015) - van Rooij, G. J.; van den Bekerom, D. C. M.; den Harder, N.; Minea, T.; Berden, G.; Bongers, W. A.; Engeln, R.; Graswinckel, M. F.; Zoethout, E.; van de Sanden, M. C. M.
Abstract : The strong non-equilibrium conditions provided by the plasma phase offer the opportunity to beat traditional thermal process energy efficiencies via preferential excitation of molecular vibrations. Simple molecular physics considerations are presented to explain potential dissociation pathways in plasma and their effect on energy efficiency. A common microwave reactor approach is evaluated experimentally with Rayleigh scattering and Fourier transform infrared spectroscopy to assess gas temperatures (exceeding 10 4 K) and conversion degrees (up to 30%), respectively. The results are interpreted on a basis of estimates of the plasma dynamics obtained with electron energy distribution functions calculated with a Boltzmann solver. It indicates that the intrinsic electron energies are higher than is favorable for preferential vibrational excitation due to dissociative excitation, which causes thermodynamic equilibrium chemistry to dominate. The highest observed energy efficiencies of 45% indicate that non-equilibrium dynamics had been at play. A novel approach involving additives of low ionization potential to tailor the electron energies to the vibrational excitation regime is proposed.